Fates and furies - Groff, Lauren (New York : Riverhead Books, 2015)
"From the award-winning, New York Times bestselling author of The Monsters of Templeton and Arcadia, an exhilarating novel about marriage, creativity, art, and perception. Fates and Furies is a literary masterpiece that defies expectation. A dazzling examination of a marriage, it is also a portrait of creative partnership written by one of the best writers of her generation. Every story has two sides. Every relationship has two perspectives. And sometimes, it turns out, the key to a great marriage is not its truths but its secrets. At the core of this rich, expansive, layered novel, Lauren Groff presents the story of one such marriage over the course of twenty-four years. At age twenty-two, Lotto and Mathilde are tall, glamorous, madly in love, and destined for greatness. A decade later, their marriage is still the envy of their friends, but with an electric thrill we understand that things are even more complicated and remarkable than they have seemed. With stunning revelations and multiple threads, and in prose that is vibrantly alive and original, Groff delivers a deeply satisfying novel about love, art, creativity, and power that is unlike anything that has come before it. Profound, surprising, propulsive, and emotionally riveting, it stirs both the mind and the heart"--
Keywords: FICTION / Literary; FICTION / Family Life; FICTION / Contemporary Women; Domestic fiction; Romance fiction